Analisis Hadis Tasyabbuh: Kehadiran Tokoh Islam Di Perayaan Bakar Tongkang Bagansiapiapi Kabupaten Rokan Hilir - Rahma Julika; Idris Siregar (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
This study examines the responses of Islamic leaders to the presence of Muslims in the Bakar Tongkang celebration in Bagansiapiapi, Rokan Hilir, Riau, with a focus on its social and theological implications. This tradition, which originated from the Chinese ethnic group, contains religious symbolism, giving rise to debates about the limits of participation in accordance with the principle of tasyabbuh. The objectives of this study are to explore the views of religious leaders, analyze the socio-theological consequences, and formulate alternative approaches to religious moderation in a multicultural society. The research method used is qualitative with a case study. Primary data were obtained through in-depth interviews with the Head of the Indonesian Ulema Council (MUI) of Rohil, representatives of the Riau Provincial Ministry of Religious Affairs, and local religious scholars, as well as direct observation of the Bakar Tongkang procession. Secondary data included classical and contemporary hadith literature, studies on religious moderation, and ethnographic studies. The analysis used the Miles & Huberman model with triangulation of sources and methods to ensure validity. The results showed that the MUI prohibited Muslims from becoming “players” in the core rituals but allowed them to be “spectators” for the sake of harmony. The Ministry of Religious Affairs emphasizes religious moderation, while local scholars emphasize respect without participation. The study recommends the narrative of “respecting without attending” and strengthening the role of institutions, education based on maqashid syariah, and inclusive cultural mediation to maintain faith and tolerance.